Efektifitas Fasilitas Umum Mall Tempat Ibadah Sebagai Penunjang Pariwisata Kota Bandar Lampung - Iqbal, Muhammad; Umar, M Abdullah; Oktavia, Rahma (Sekolah Tinggi Ilmu Ekonomi Syariah (STIES) ALIFA, 2024)
Bandar Lampung has a strategic location and of course has quite a lot of tourist destinations. Tourism in Bandar Lampung is quite diverse, ranging from Hills, Beaches, Museums, Artificial Tourist Attractions and Malls. The purpose of the study was to see the effectiveness of public facilities in the form of places of worship as a support for tourism in Bandar Lampung. This research method is a qualitative method. Data sources were obtained from researchers visiting research objects and conducting surveys, then the survey results were studied using theories related to Sharia management, then presented and conclusions were drawn. The research objects that the researchers used were 8 large malls in Bandar Lampung. The results of the study were 1) All malls in Bandar Lampung have provided prayer room facilities as places of worship. 2) The prayer rooms provided have met the provisions of Islamic Sharia but are still not in the category of upholding the specialness of worship. The prayer room is only limited to users being able to perform worship. 3) In the category of needs and comfort, the prayer rooms in the mall in Bandar Lampung City still need to be improved to a higher level, because the provision of facilities and cleanliness of the prayer rooms still need attention from managers or even the local government.